Dual-band dual-polarization microstrip antenna - Vishwakarma R.K.; Vishvakarma B.R. (My University, 2025)
The analysis of single patch microstrip antenna based on impedance model emphasizing mainly on the design considerations for dual-band and dual-polarization, is presented here. A length compensation technique is proposed to achieve the exact dual mode resonance with desired accuracy. The proposed method provides serval alternative dimensions (lengths) of the patch which could be utilized to develop the dual-band, dual-polarization antenna.